The Role of IR in Pediatric Liver Cancer - Acord, Michael R.; Aguado, Allison; Gill, Anne E. (Seminars in Interventional Radiology, 2025)
Despite the well-defined role of interventional radiology (IR) in the management of adult patients with hepatocellular carcinoma (HCC), the role of IR for pediatric liver tumors is still being established. This is, in part, due to the rarity and heterogeneity of pediatric liver tumors as well as the limited literature supporting liver-directed therapies for children. In addition, hepatoblastoma, the most common primary pediatric liver tumor, carries a good prognosis with current surgical and systemic treatment options directed by well-established clinical trials. Still, a subset of patients will not be amenable to operative treatment, and other pediatric liver tumors, such as HCC, portend a dismal prognosis. These settings offer opportunities for growth of pediatric IR and to provide services that improve the lives of children. The purpose of this article is to review the role of IR in pediatric liver cancer, including biopsy recommendations set forth by current clinical trials, transarterial chemoembolization and radioembolization, and percutaneous ablation.
Keywords: liver cancer; pediatric; interventional radiology; ablation; embolization; biopsy